Preemptive antibiotic strategies for gram-positive bacteria in preservation fluid: a single-center experience - Li, Jianming; Li, Jianyi; Li, Jun; Fu, Qian; Wu, Chenglin; Zhang, Huanxi; Su, Xiaojun; Liu, Longshan; Wang, Changxi (Frontiers in Medicine, 2025)
ObjectiveTo elucidate the risk stratification of gram-positive bacteria in the preservation fluid (PF), investigate antibiotic resistance and its role in early post-kidney transplant infections, and assess the efficacy of preemptive-anti-Gram-positive antibiotic (P-antiGP) therapy.MethodsThis retrospective study analyzed the clinical data of 144 kidney transplant donors and 218 recipients between April 2015 and October 2020. Recipients with any of the high-virulence gram-positive bacteria (such as Enterococcus faecium, Enterococcus faecalis, and Staphylococcus aureus) in PF were defined as high-risk group. Recipients with other pathogens in PF were defined as low-risk group.ResultsThe high-risk group had a significantly higher incidence of infection events as compared with the low-risk group (42.6% vs. 26.2%, p = 0.014). Multivariate analysis indicated a trend toward an increased risk of early post-transplant infections in the high-risk group (adjusted OR = 1.855, 95% CI: 0.991–3.464, p = 0.052). Seven recipients (1.5%) were diagnosed as possible donor-derived infections (P-DDIs) and all of them were from the high-risk group. 56.4% (123/218) of recipients had multidrug-resistant organisms (MDROs) in PF and 12.4% (27/218) had extensively-resistant organisms (XDROs). The P-DDIs rate was notably higher in the extensively drug-resistant (XDR) group than non-XDR group (11.1% vs. 2.1%, p = 0.014). The incidence of P-DDIs was significantly lower (p = 0.025) in recipients with P-antiGP therapy (4.3%) as compared to recipients who did not (23.8%).ConclusionE. faecium, E. faecalis, and S. aureus in PF are considered high-virulence gram-positive bacteria, and recipients with these pathogens are categorized as high-risk group. Additionally, a high prevalence of antibiotic resistance exists among gram-positive bacteria in PF, correlating with post-transplant infections. Furthermore, The addition of P-antiGP therapy as a preemptive therapy in the high-risk group can effectively reduce the incidence of P-DDIs.